2019
DOI: 10.3390/ijms20123059
|View full text |Cite
|
Sign up to set email alerts
|

New Lectins from Mediterranean Flora. Activity against HT29 Colon Cancer Cells

Abstract: Experiments conducted in vitro and in vivo, as well as some preclinical trials for cancer therapeutics, support the antineoplastic properties of lectins. A screening of antitumoral activity on HT29 colon cancer cells, based on polypeptide characterization and specific lectin binding to HT29 cells membrane receptors, was performed in order to assess the bioactivities present in four Mediterranean plant species: Juniperus oxycedrus subsp. oxycedrus, Juniperus oxycedrus subsp. badia, Arbutus unedo and Corema albu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The O-glycans are attached to six of the nine S/T residues in the N-terminal tryptic peptide of insulin β-chain (Sparrow et al, 2007), suggesting that γconglutin may show specificity to these domains as it is galactosespecific (Ribeiro et al, 2014). Others authors (Klein et al, 2009) reported that the accumulation of INS-1 Ser1011 GlcNAc in HepG2 In this work, HepG2 cell membranes purified by an optimized methodology (Oliveira et al, 2019;Vercoutter-Edouart et al, 2008) were analyzed by 1D and 2D (IEF/SDS-PAGE-R) electrophoresis for proteomic profiling (Figure 4a,b) analysis, followed by glycodetection of polypeptide profile of these membranes(Figure 4c), for INS-1 detection as identified in Figure 4a,b,c. The glycoprotein profile of HepG2 cell membranes revealed a relatively simple pattern comprising a few glycoproteins, with the INS-1 receptors localized at the MW described of 130 kDa, for the heavy polypeptide chain, when compared to mucin control of 50 KDa, with two isoforms with pI around 3.8 and 4.1, and of 95 kDa for the lower polypeptide chain with pI near pH 4.5 (Figure 4b).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The O-glycans are attached to six of the nine S/T residues in the N-terminal tryptic peptide of insulin β-chain (Sparrow et al, 2007), suggesting that γconglutin may show specificity to these domains as it is galactosespecific (Ribeiro et al, 2014). Others authors (Klein et al, 2009) reported that the accumulation of INS-1 Ser1011 GlcNAc in HepG2 In this work, HepG2 cell membranes purified by an optimized methodology (Oliveira et al, 2019;Vercoutter-Edouart et al, 2008) were analyzed by 1D and 2D (IEF/SDS-PAGE-R) electrophoresis for proteomic profiling (Figure 4a,b) analysis, followed by glycodetection of polypeptide profile of these membranes(Figure 4c), for INS-1 detection as identified in Figure 4a,b,c. The glycoprotein profile of HepG2 cell membranes revealed a relatively simple pattern comprising a few glycoproteins, with the INS-1 receptors localized at the MW described of 130 kDa, for the heavy polypeptide chain, when compared to mucin control of 50 KDa, with two isoforms with pI around 3.8 and 4.1, and of 95 kDa for the lower polypeptide chain with pI near pH 4.5 (Figure 4b).…”
Section: Discussionmentioning
confidence: 76%
“…Goldstein et al ( 1980 ) defined lectin as a "protein or glycoprotein of non‐immune origin (thus excluding immunoglobulins) which bind in a stable manner (thus excluding enzymes and carbohydrate sensor/transport proteins) to carbohydrates.” Plant lectins exert a vast panel of bioactivities (Ribeiro et al., 2018 . Lupinus albus is a legume whose seeds contain reserve proteins exhibiting an array of bioactivities as wide as insecticide, fungicide (Monteiro et al., 2015 ), anticancer (Oliveira et al, 2019 ), and hypoglycemic (Fornasini et al., 2012 ; González‐Santiago et al., 2017 ; Magni et al., 2004 ; Terruzzi et al., 2011 ). Some of these proteins are lectins, with γ‐conglutin and BLAD (Ribeiro et al, 2014 ) as examples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, bitter melon-mediated modulation in different signaling events might be due to modulation of membrane lipid rafts. Lectin-type compounds are found to bind specifically to cell surface oligosaccharides and glycan, and are transported into cells [96,97]. Cancer cells modulate their membrane structure from normal cells in many ways.…”
Section: How Does Bitter Melon Extract Enter Into Cancer Cells?mentioning
confidence: 99%
“…Among them, alteration in membrane oligosaccharides is observed predominantly in cancer cells [97]. Different types of lectins are present in bitter melon extract, which may act similarly to enter specifically into cancer cells and exhibit biological mechanisms including inhibition of ribosomes and induction of apoptotic and autophagic cell death [96,98]. Different triterpene glycosides bind to cell membranes, interact with membrane lipids and form glycoside-sterol complexes in the membrane, resulting in the formation of multimeric channels in sterol-containing lipid bilayers and increased permeability of membranes to ions and peptides [99].…”
Section: How Does Bitter Melon Extract Enter Into Cancer Cells?mentioning
confidence: 99%